Enforcement of refugee rights in South Africa through public interest litigation in the spirit of Ubuntu - Baldauf, Marie Charlotte (Department of Public Law, 2024)
This master's thesis addresses the challenge of ineffective enforcement of refugee rights in South Africa, focusing on the right of refugees to seek and enjoy asylum and undergo a fair refugee status determination procedure. The dissertation proposes a solution through the exploration of public interest litigation (PIL) as a method to support refugees in asserting their rights. The central argument posits that enforcing refugee rights through PIL aligns with the African philosophy of Ubuntu, emphasizing interconnectedness and humanity. The thesis contends that PIL, deeply rooted in Ubuntu, can serve as a catalyst for change, fostering a compassionate and inclusive approach to refugee protection in South Africa. The dissertation examines the compatibility between Ubuntu and human rights principles, showcasing Ubuntu as a persuasive tool in PIL cases advocating for refugee rights. The thesis challenges critiques against the applicability of Ubuntu in a legal setting and advocates for acknowledging its potential to serve as a foundation for public morality. Utilizing Ubuntu as an interpretive instrument creates opportunities to incorporate a wide range of human rights into legal discussions, offering a guiding structure for addressing persistent disputes concerning justice. By invoking Ubuntu in PIL, legal practitioners can safeguard constitutional rights while promoting broader public interest and transformative societal change. The research delves into the provisions of international refugee law and domestic South African law, enriched by a comprehensive review of various published articles, journals, and case law related to PIL concerning access to refugee status determination procedures in South Africa. The thesis concludes by asserting that through justice, empathy, and solidarity, the enforcement of refugee rights becomes a manifestation of South African societal values. By embracing the spirit of Ubuntu, South Africa has the potential to emerge as a beacon of hope and a model for effective refugee protection globally